Imigração portuguesa e hospitalidade: Casa de Portugal de São Paulo e seus eventos (1980-2010) - Fernandez, Leandro Rodrigues Gonzales (2016)
This investigation takes place in the field of cultural history and unveils the history of São Paulo‟s House of Portugal, approached through its identity pathways. To this end, the focus is on the most frequently held events in the association, their origin, and their meanings. The cultural program analysis rebuilds the associations and Portugal‟s political-cultural path, as well as memories are ransomed and reconstructed in the Luso-Brazilian context. The research differential lies on historicizing the hospitality within the e/immigration process, contextualizing the departures from Portugal and arrivals in the state of São Paulo, welcoming in the Portuguese way, the flavors, tastes, and traditions recollected in the practice of table-sharing and musical entertainment. The sources and interviews held with the Board and people linked to the association point to a duality featuring the Portuguese identity between tradition and modernity, besides indicating that the House of Portugal has politically reflected the Portuguese cultural actions since it was founded by the National Program Secretariat, thus presenting remainders of the Salazarian cultural heritage